Make prints! - Solga, Kim. (Danbury, CT : Grolier, Inc., 1993)
Presents step-by-step instructions for printing colorful impressions using a variety of materials and surfaces.
Keywords: Prints -- Technique -- Juvenile literature; Prints -- Technique